Use of Recycled Ceramic Powder as a Green Alternative in Mortar-Based Cementitious Composites - Zghair, Luma A. G.; Yousif, Mohammad Z.; Salman, Luay K.; Al-Hamd, Rwayda Kh. S.; Sarhan, Mazin M. (Civil Engineering Journal, 2024)
Recognizing material waste as a significant global concern has influenced both the environment and the construction industry. The utilization of ceramic waste as a recycled material in construction projects has gained attention as an effective and sustainable approach to address environmental issues. This study examines the use of waste ceramic tile powder (WCTP) as a supplementary material in cement mortars to decrease the amount of cement required. WCTP was used in place of cement at percentages of 5%, 10%, and 20%. Four different mix designs were created and tested for the study, yielding a total of 48 specimens. Numerous investigations were carried out, including flow table evaluations, measures of dry density, assessments of compressive and flexural strengths, X-ray diffraction, and SEM-EDX testing. The objective of these investigations was to evaluate the specimens' mechanical and physical characteristics as a whole. The findings showed that using ceramic powder in place of some cement might enhance the properties of the mortar. The compressive and flexural strengths of the mortar were notably impacted by replacing 10% of the cement content with ceramic powder. The inclusion of ceramic powder significantly enhanced the mortar's microstructure interface, according to SEM-EDX studies. In the end, the utilization of ceramic powder was found to have a substantial positive impact on the environment by reducing waste. Doi: 10.28991/CEJ-2024-010-10-03 Full Text: PDF